2016
DOI: 10.17509/jrak.v4i2.4043
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kinerja Reksadana Syariah

Abstract: Abstract. This study aims to determine the performance of Islamic Mutual Funds in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
1
8
0
2
Order By: Relevance
“…Researches on the performance analysis of Sharia mutual funds have also been conducted by several previous researchers, such as a research by Waridah and Mediawati (2016) which examined specifically on the Sharia equity mutual fund instruments using Sharpe Ratio performance measurement method during the 2010-2014 period. It was concluded that Cipta Syariah Equity mutual fund was the best performing Sharia mutual fund with Sharpe ratio of -0.349 and PNM Ekuitas Syariah became the lowestperforming Sharia mutual fund during that period with a Sharpe ratio of -1.232.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Researches on the performance analysis of Sharia mutual funds have also been conducted by several previous researchers, such as a research by Waridah and Mediawati (2016) which examined specifically on the Sharia equity mutual fund instruments using Sharpe Ratio performance measurement method during the 2010-2014 period. It was concluded that Cipta Syariah Equity mutual fund was the best performing Sharia mutual fund with Sharpe ratio of -0.349 and PNM Ekuitas Syariah became the lowestperforming Sharia mutual fund during that period with a Sharpe ratio of -1.232.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This positive trend proves that investment, especially in capital markets, is increasingly becomes a necessity for society. However, Waridah and Mediawati (2016) said that there are obstacles for investors to be able to invest funds in the capital market, such as the knowledge, information or limited time. Thus, alternative investment instruments that can be used as a solution to these barriers are mutual funds (Pangestuti et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sebaiknya para investor untuk dapat berpikir bijak mengenai pilihan instrumen pilihannya untuk tidak hanya memperhatikan aspek emosional semata tetapi dengan pertimbangan spiritual dan beberapa analisis kinerja yang tepat (Waridah & Mediawati, 2016). (2015)(2016)(2017).…”
unclassified